Fast range measurement of spot scanning proton beams using a volumetric liquid scintillator detector. (30th July 2015) - Hui, Cheuk Kai; Robertson, Daniel; Alsanea, Fahed; Beddar, Sam
Abstract: Accurate confirmation and verification of the range of spot scanning proton beams is crucial for correct dose delivery. Current methods to measure proton beam range using ionization chambers are either time-consuming or result in measurements with poor spatial resolution. The large-volume liquid scintillator detector allows real-time measurements of the entire dose profile of a spot scanning proton beam. Thus, liquid scintillator detectors are an ideal tool for measuring the proton beam range for commissioning and quality assurance. However, optical artefacts may decrease the accuracy of measuring the proton beam range within the scintillator tank. The purpose of the current study was to (1) develop a geometric calibration system to accurately calculate physical distances within the liquid scintillator detector, taking into account optical artefacts; and (2) assess the accuracy, consistency, and robustness of proton beam range measurement using the liquid scintillator detector with our geometric calibration system. The range of the proton beam was measured with the calibrated liquid scintillator system and was compared to the nominal range. Measurements were made on three different days to evaluate the setup robustness from day to day, and three sets of measurements were made for each day to evaluate the consistency from delivery to delivery. All proton beam ranges measured using the liquid scintillator system were within half a millimeter of the nominal range. The delivery-to-delivery standard deviation of the range measurement was 0.04 mm, and the day-to-day standard deviation was 0.10 mm. In addition to the accuracy and robustness demonstrated by these results when our geometric calibration system was used, the liquid scintillator system allowed the range of all 94 proton beams to be measured in just two deliveries, making the liquid scintillator detector a perfect tool for range measurement of spot scanning proton beams.